Collaboration between East and West: influence of consumer dialectical self on attitude towards co-brand personality traits. Issue 6 (26th May 2020) - Wang, Weisha; Chen, Cheng-Hao Steve; Nguyen, Bang; Shukla, Paurav
Abstract : Purpose: With rising globalization, Western and Eastern brands are increasingly collaborating and co-branding. Drawing on the theory of dialectical self that captures the degree of cognitive tendency to tolerate conflicts, inconsistencies and ambiguities in self-concept, this paper investigates the effect of consumer dialectical self on co-branding that encompasses Western and East Asian cultural brand personality traits. Design/methodology/approach: Two studies were conducted using Chinese participants to examine the effects of the dialectical self on co-brand evaluation under single-and dual-personality conditions and to explore the mediating role of ideal social self-congruence and the moderating role of product type (high vs low conspicuous). Findings: The findings suggest that counterintuitive to the received wisdom, the dialectical self negatively influences one's attitude towards a co-brand in the dual-personality condition only. Further, ideal social self-congruence mediates the relationship between the dialectical self and dual-personality co-brand evaluation in the high conspicuous product condition only. Practical implications: Important implications are offered to international marketing managers for managing the dialectical self that lead to positive co-brand evaluations. Moreover, managers should highlight ideal social self-congruence for co-branding success for particular product types. Originality/value: This paper examines co-branding from a novel perspective of consumer dialectical self and shows the pivotal role it plays when brands carry varying cultural traits engage in co-branding. By identifying the role of the dialectical self and the important mediator and moderator, the paper fulfils an important gap in co-branding literature and offers key implications.